Decentering Whiteness in Libraries: A Framework for Inclusive Collection Management Practices - Jamison, Andrea (Rowman & Littlefield Publishers, 2023)
The book serves as a "how to" guide for evaluating and crafting collection development policies that will help create equity and diversity in library collections.
Keywords: 2023-10 October